Otolaryngology Providers Must Be Alert for Patients with Mild and Asymptomatic COVID‐19. (14th April 2020) - Cheng, Xiaoting; Liu, Jialin; Li, Ning; Nisenbaum, Eric; Sun, Qing; Chen, Bing; Casiano, Roy; Weed, Donald; Telischi, Fred; Denneny, James C.; Liu, Xuezhong; Shu, Yilai
Abstract : More than half of COVID‐19 patients are afebrile early in the disease course, yet mildly ill or asymptomatic patients can still spread SARS‐CoV‐2 with high efficiency. Atypically presenting patients may be seen in noninfectious disease settings such as otolaryngology, which is a specialty prone to occupational exposure. Otolaryngologists have been infected with COVID‐19 at higher rates than other specialties in China and other countries. Otolaryngology providers should maintain high clinical suspicion for mild and asymptomatic COVID‐19 patients. Protective strategies should be implemented including preappointment screening, triaging, restriction of nonurgent visits and surgeries, telemedicine, and appropriate personal protective equipment use.